Differences in tree and shrub establishment due to tree guard type in a temperate upland pasture. (14th March 2018) - Brown, Sharon L.; Reid, Jackie; Reid, Nick; Smith, Rhiannon
Summary: Success of establishing native trees in cool temperate environments depends on the ability of seedlings to withstand subzero temperatures and recurrent frosts. This study compared the survival and growth of five tree and shrub species with two guard types at three landscape positions in an upland pasture. Seedlings were planted between December 2013 and March 2014. Half of the seedlings were planted in tall Corflute ® guards (60 cm high), and the remaining seedlings were interplanted in milk cartons (30 cm). Seedling survival and height were measured in November 2014. Hourly temperature readings were recorded between March and November 2014. Seedling height for all species was greater in tall guards than milk cartons at all landscape positions, possibly at least partly due to etiolation. However, seedlings in tall guards survived better than seedlings in milk cartons at mid‐ and upper‐slope positions. Higher temperatures may have benefited seedling performance by prolonging the growing season as average maximum temperature was significantly higher inside tall guards than milk cartons and ambient conditions at all landscape positions. Average daily temperature was significantly higher in tall guards compared to milk cartons and ambient conditions at the upper‐slope site only. There were no significant differences in average minimum temperature between guard types at all landscape positions.